The Genesis of the Scientific School of Accounting of Nizhny Novgorod State University Named After N. I. Lobachevsky in the System of Development of Economic Knowledge - I. E. Mizikovskii (Учёт. Анализ. Аудит, 2024)
Accounting science, as well as science in general, is in constant development and search for new forms, methods and concepts that are immanently embedded in the system of improving economic management. The purpose of the article is to scientifically argue the relevance of accounting knowledge as an integral part of economics on the example of the genesis of the scientific school of Doctor of Economics, Professor E. A. Mizikovsky. The results of accounting and  analytical studies play a significant role in structuring the information and instrumental space of corporate management of business entities; in the development of managerial, production and tax accounting; in the formation of a scientific basis for audit and internal control; allow you to create a solid methodological basis for accounting (financial) accounting and auditing standards, strategies for their incorporation into advanced management practices. A significant achievement of scientific accounting thought is the successful development and widespread implementation of the Accounting Plan and Instructions for its application, flexibly adapted to the complex realities of economic life, the needs of public and corporate governance. In the course of the research, methods of historicism, structural-functional and systemic types of analysis were used; formalization, interpretation, evaluation and systematization of scientific data; a causal approach was applied. The article reflects the contribution of the scientific accounting school of Nizhny Novgorod State University named after N. I. Lobachevsky to the development of accounting and the formation of accounting science as a key, formative element of the system of economic knowledge and a catalyzing factor in the development of corporate management of enterprises.